The Araucaria Project. The distance to the Sculptor group galaxy NGC 7793 from near-infrared photometry of Cepheid variables - Zgirski Bartlomiej; Gieren Wolfgang; Pietrzyński Grzegorz; Karczmarek Paulina; Górski Marek; Graczyk Dariusz; Pilecki Bogumil; Taormina Mónica; Suchomska Ksenia; Wielgórski Piotr; Konorski Piotr (EPJ Web of Conferences, 2017)
We performed deep near-infrared J and K photometry of a field in the Sculptor Group spiral galaxy NGC 7793 using ESO VLT and HAWK-I instrument. We produced a sample of 14 Cepheids whose locations and periods of pulsation were known from our previous paper on distance determination to this galaxy based on V and I bands. We determined mean J and K magnitudes based on measurements from two nights and produced period-luminosity relations for both filters. Using those near-infrared dependencies together with relations for bands V and I obtained before, we were able to obtain true distance modulus for NGC 7793. We also calculated the mean reddening affecting our Cepheids.